How has labor demand been affected by the COVID-19 pandemic? Evidence from job ads in Mexico - Raymundo M. Campos-Vázquez; Gerardo Esquivel; Raquel Y. Badillo (Latin American Economic Review, 2021)
There is a concern among social scientists and policymakers that the COVID-19 crisis might permanently change the nature of work. We study how labor demand in Mexico has been affected during the pandemic by web scraping job ads from a leading job search website. As in the U.S., the number of vacancies in Mexico declined sharply during the lockdown (38 percent). In April there was a change in the composition of labor demand, and wages dropped across the board. By May, however, the wage distribution and the distribution of job ads by occupation returned to their pre-pandemic levels. Overall, there was a slight decline in specific requirements (gender and age), no change in required experience, and a temporary increase in demand for low-skilled workers. Contrary to expectations, opportunities for telecommuting diminished during the pandemic. Using a simple Oaxaca-Blinder decomposition, we find that the variation in the average advertised wage in April is explained more by a higher proportion of low-wage occupations than by a reduction in the wages paid for particular occupations. In sum, we find no evidence of a significant or permanent change in labor demand during the pandemic in Mexico.
Keywords: J20; J23; J30; J60; O54; 330; Job ads; Labor demand; Employment; Wag-es; COVID-19; Mexico